Seasonal changes in pituitary and plasma prolactin concentrations, and the role of Prolactin in the control of delayed implantation in female Miniopterus schreibersii - Bojarski, Christina (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1993)
Mammotropes were successfully identified in the anterior pituitary gland of Miniopterus schreibersii using immunocytochemical (ICC) staining at the light and electron microscopy level. Mammotropes were distributed throughout the gland, were polygonal in shape and during secretory activity contained numerous large secretory granules (350 - 800nm). Using double ICC labelling, prolactin and growth hormone were never co-localiszed and found in individual cells only. Plasma prolactin levels were successfully measured on a monthly basis using radioimmunoassay and monthly pituitary prolactin levels were quantified using morphometric analysis of immunogold ICC staining and densitometry with polyacrylamide gels. Seasonal changes in the ultrastructure of mammotropes, and pituitary and plasma prolactin concentrations in female Miniopterus schreibersii indicated that there was an increase in prolactin secretion during the second half of the period of delayed implantation and that prolactin secretion remained elevated during normal embryonic development and lactation. This suggests that prolactin may be part of the luteotropic and lactogenic complex, and that the hormone might be responsible for terminating the period of delayed implantation. The latter is supported by experiments, where exogenous prolactin initiated precocious implantation during early delayed implantation, and treatment with bromocryptine (which inhibits prolactin synthesis) retarded implantation. Activation of mammotropes to synthesise prolactin and an increase of plasma prolactin levels occurred shortly after the winter solstice (21 June), suggesting that increasing daylength may be the environmental cue, which terminates the period of delayed implantation in Miniopterus schreibersii.
Keywords: Bats -- Reproduction; Prolactin -- Research; Pituitary hormones; Zoology, Experimental